A blue luminescent MOF as a rapid turn-off/turn-on detector for H2O, O2 and CH2Cl2, MeCN: 3∞[Ce(Im)3ImH]·ImH1. Issue 9 (7th March 2015) - Meyer, L. V.; Schönfeld, F.; Zurawski, A.; Mai, M.; Feldmann, C.; Müller-Buschbaum, K.
<x xml:space="preserve">Abstract</x> A blue emitting MOF is presented as a fast turn-off/turn-on detector for various analytes utilising 5d–4f-transitions of Ce3+.